2022
DOI: 10.31557/apjcp.2022.23.1.109
|View full text |Cite
|
Sign up to set email alerts
|

TP53 and EGFR Mutational Status in Thymoma: A Genetic Sequencing Study

Abstract: Thymoma staging, histologic type, and complete eradication through any treatment modalities are significant to increase the survival of patients and reduce its recurrence rate. Prognosis of thymoma is worse at higher stages of the disease. The patients at the advanced stage of the thymoma have a 5-year median survival of 69%. Currently, the treatment choice in thymoma is surgery providing a better prognosis (Detterback et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…TP53 Exon 6 mutations, including both missense and nonsense mutations, were also detected only in 7.4% of cases. Both results suggest a limited role of EGFR and TP53 in the pathogenesis of thymomas [8]. TP53 mutations, however, seem to be prominent in TCs, especially in their highly aggressive forms [9].…”
Section: Next Generation Sequencingmentioning
confidence: 81%
See 2 more Smart Citations
“…TP53 Exon 6 mutations, including both missense and nonsense mutations, were also detected only in 7.4% of cases. Both results suggest a limited role of EGFR and TP53 in the pathogenesis of thymomas [8]. TP53 mutations, however, seem to be prominent in TCs, especially in their highly aggressive forms [9].…”
Section: Next Generation Sequencingmentioning
confidence: 81%
“…The key tumor-suppressor genes, P53 (TP53) and EGFR, commonly mutated in human cancers, have also been scrutinized in thymomas. A recent study by Syahruddin et al identified EGFR Exon 18 mutation (E709K) and a nonsense mutation in a small subset of 7.4% of cases [8]. TP53 Exon 6 mutations, including both missense and nonsense mutations, were also detected only in 7.4% of cases.…”
Section: Next Generation Sequencingmentioning
confidence: 96%
See 1 more Smart Citation